Can Regional Decentralisation Shift Health Care Preferences? - Joan Costa-i-Font; Ada Ferrer-i-Carbonell (Center for Economic Studies and ifo Institute (CESifo), 2017)
Uniform health care delivered by a mainstream public insurer - such as the National Health Service (NHS), seldom satisfies heterogeneous demands for care, and some unsatisfied share of the population either use private health care, or purchase private insurance (PHI). One potential mechanism to partially satisfy heterogeneous preferences for health care, and discourage the use of private health care, is regional health care decentralisation. We find robust estimates suggesting that the development of regional health services shifted both perceptions of, and preferences for, using the NHS, making it more likely individuals would use public health care and, consequently, reducing the uptake of PHI. These results are heterogeneous by income, education, and age groups; and are robust to placebo and other robustness and falsification checks.
Keywords: H70; I18; 330; National Health Service (NHS); political decentralization; use of private health care; private health insurance; health system satisfaction; demand for private health care